Dynamical mechanical properties and microstructure characteristics of cemented tailings backfill considering coupled strain rates and confining pressures effects. (21st February 2022) - Zheng, Di; Song, Weidong; Cao, Shuai; Li, Jiajian
Highlights: Confining pressure effect on dynamical mechanical properties of cemented tailings backfill (CTB) was investigated. Increasing the average strain rate (ASR) led to a remarkable increase in CTB's dynamic peak compressive strength (DPCS) under confining pressure. The fitting equations were developed to forecast the relationship between impact amplitude and DPCS under confining pressure. Microstructural characteristics of CTB after SHPB test with confining pressure were obtained through CT techniques. Abstract: This paper discusses the relationship between the average strain rate (ASR), confining pressure, dynamic peak compressive strength (DPCS), and cemented tailings backfill (CTB) crack volume through the SHPB test and microscopic computed tomography (CT). The CTB samples with a water-cement ratio of 1:4 and a slurry concentration of 75% were prepared to carry out SHPB tests with different ASR (25.6 ∼ 104.73 s −1 ), different ASR (12.16 ∼ 152.05 s −1 ) at different confining pressures (0.5 ∼ 2 MPa). The results show that with the increase of ASR when there is no confining pressure, the DPCS shows a trend of first increasing and then decreasing. However, when the confining pressure is 0.5 and 1 MPa, the DPCS increases linearly. When the confining pressure is 1.5 and 2 MPa, the DPCS increases exponentially and logarithmically, respectively. The micro-CT analysis shows that the total crack volume generated after the SHPB rises first and then falls with the increase of the ASR under confining pressure of 1 MPa. When the impact amplitude is 150 mV, the crack volume also decreases with the improvement of the confining pressure (0.5–2 MPa). The internal cracks of the CTB change from shear cracks to tensile cracks, and the initial pores of the samples first decrease and then increase. The failure pattern of all CTB samples by SHPB was mainly shear, tensile, and hybrid failure (shear and tensile). The research results can provide a valuable reference for the dynamic performance of CTB under confining pressure and the design of mining backfill.